Variability in susceptibility of voles (Arvicolinae) to experimental infection with Cryptosporidium muris and Cryptosporidium andersoni - Modrý, David; Hofmannová, Lada; Antalová, Zuzana; Sak, Bohumil; Kváč, Martin (Parasitology research, 2012)
The infectivity of Cryptosporidium muris and Cryptosporidium andersoni in various species of voles was studied using experimental infections. None of the experimental voles inoculated with 1 × 10(5) oocysts of Cryptosporidium spp. shed any oocysts during 40 DPI, except Brandt's vole (Lasiopodomys brandtii), which was susceptible to C. muris infection. Experiments confirmed the resistance of voles of the genus Microtus sensu stricto to infection with mammalian gastric cryptosporidia, which provides a new study model with prospects to more fully understand the processes involved in the phenomenon of host specificity of this group of protists.
Keywords: Disease Models, Animal; modely nemocí na zvířatech; Disease Resistance; zvířata; Host Specificity; odolnost vůči nemocem; kryptosporidióza; Cryptosporidium; hostitelská specificita; Cryptosporidiosis; Arvicolinae; Animals